The real value to the mining industry of leading-practice waste management - Bentel, G.M. (Mine Waste 2010: Proceedings of the First International Seminar on the Reduction of Risk in the Management of Tailings and Mine Waste, 2010)
Mining wastes waste rock, process tailings, and other mining by-products have little beneficial use or value. If not managed well, some wastes can leave an enduring threat of serious health and/or environmental harm, and hence good waste management practice can significantly increase both capital and operating costs. Some mining waste can cause serious health and environment issues, and therefore responsible waste management is a key attribute of sustainable mining. When poor or irresponsible waste management is discovered and publicised through the media, the responsible company can suffer serious detrimental consequences through public outrage and loss of stakeholder and shareholder confidence and support. While not exactly a waste management issue, the public (including President Obama) and shareholder reaction (Figure 1) to the BP Deepwater Horizon incident that resulted in the loss of 11 lives, 17 injured, and that continues to wreak untold environmental damage, illustrates societys perception of the social and financial implications of a catastrophic environmental incident.